The impact of soccer training on the immune system - Rebelo, A. N.; Candeias, J. R.; Fraga, M. M.; Duarte, J. A.; Soares, J. M.; Magalhaes, C.; Torrinha, J. A. (The Journal of Sports Medicine and Physical Fitness, 1998)
OBJECTIVE: The aim of this study was to evaluate whether the level of some immune markers changed in soccer players during pre-season and during playing-season. DESIGN: An observational study for one soccer season (one year). SETTING: Professional soccer players. PARTICIPANTS: Thirteen professional soccer players (age: 26.3 +/- 3.7 years). MEASURES: The effect of 11 months of soccer training sessions and matches on circulating leukocyte and lymphocyte subpopulations was investigated. Blood samples were taken before the season and also 6 weeks, 6 months and 11 months later. All samples were taken at 08:00 h. RESULTS: Total lymphocyte counts did not change in all samples. During the pre-season, however, the concentrations of some inflammatory lymphocyte subpopulations were changed: CD4CD45RA+ was elevated and CD57 and CD8CD57 showed a significant decrease (p < 0.05), At the competitive period, CD4 and CD8 were increased. At the end of the season there were significant changes in some immune cells: total leukocyte and neutrophil number and CD8+ cell concentration was increased compared to pre-season values and the CD4/CD8 ratio was decreased. CONCLUSIONS: The results suggest that athletes exposed to a long-term training periods can exhibit variations in some immune cells. The clinical significance of these variations requires more detailed investigation.